Crowd evacuation simulation for walking-along-side effect in the Stadium - Liang Benbu (MATEC Web of Conferences, 2020)
With growing concerns about stadiums where attract large mass gathering, modeling and simulating crowd evacuation is pertinent to ensuring efficient and safe conditions. Based on the modified social force model and multi-agent simulation, several simulation scenarios are conducted to study the walking-along-side effects. The results show that walking along the sides will increase evacuation time, but it can mitigate the pressure of clogging effects and stream arching queue. Meanwhile, walking-along-side effects can relieve the density pressure of the exit and the "fast-is-slow" phenomenon. At last, several suggestions are put forward to promote evacuating capacity of the stadium.